Professional English Communication for Engineers in Nepal - Agrawal, Santosh (Journal of Advanced Academic Research, 2017)
This article is focused on the nature, needs and problems of the professional communications of the engineers in Nepal. It includes a number of significant aspects of the engineering professional communication with the use of English language. The study is an outcome of a survey of several aspects of the engineering profession, study of several relevant literature and the contact to a number of experts associated with the field of professional communication. The researchers in the field of professional communication require being more and more specific according to the changing specific needs of the professionals in the modern context today. It is necessary to pinpoint the nature of engineering professional skills, in order to save the time and other resources, if they are not properly utilized to achieve the set goals. The researchers in the past along with the students over here, are aware of the necessity of making more and more researches in the field of professional communication of the engineers in order to minimize the communicative problems of the engineers on one hand and to show a proper and adequate specific path in the areas of teaching and learning the specific skills of communication on the other. The sole purpose of the present research article is to indicate a number of measures to be applied to better the communicative situations of the engineers both during their study and at work. Hence a number of tentative suggestions and recommendations have been drawn following the conclusion of the article. Journal of Advanced Academic Research Vol. 3, No. 2, 2016, page: 14-21